A multi-region coupling scheme for compressible and incompressible flow solvers for two-phase flow in a numerical wave tank. (13th February 2016) - Martínez Ferrer, P.J.; Causon, D.M.; Qian, L.; Mingham, C.G.; Ma, Z.H.
Highlights: We have presented a novel finite-volume coupling strategy. Incompressible and compressible two-phase solvers were successfully coupled. Compressibility and aeration effects were verified against other data. Abstract: We present a multi-region coupling procedure based on the finite-volume method and apply it to two-phase hydrodynamic free surface flow problems. The method combines the features of one incompressible and one compressible two-phase flow solvers to obtain a coupled system which is generally superior to either solver alone. The coupling strategy is based on a partitioned approach in which different solvers, pre-defined in different regions of the computational domain, exchange information through interfaces, i.e. areas separating these regions. The interfaces act as boundary conditions passing the information from one region to the other mimicking the finite-volume cell-to-face interpolation procedures. This results in high performance computing coupled simulations whose functionality can be further extended in order to build a generic numerical wave tank accounting for incompressible flow regions as well as compressibility and aeration effects. We select a series of preliminary benchmarks to verify this coupling procedure which includes the simulation of a hydrodynamic dam break, the propagation and reflection of regular waves, the convection of an inviscid vortex, pseudocavitation, a water column free drop in a closed tank and a plunging wave impact at a vertical wall. The obtained results agree well with exact solutions, laboratory experiments and other numerical data.